Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fimmu.2020.593103
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fatty Acid Synthesis Leads to Subset Imbalance and IFN-γ Overproduction in T Helper 1 Cells

Abstract: Recent reports have shown the importance of IFN-γ and T-bet+ B cells in the pathology of SLE, suggesting the involvement of IFN-γ-producing T-bet+ CD4+ cells, i.e., Th1 cells. This study determined the changes in Th1 subsets with metabolic shift and their potential as therapeutic targets in SLE. Compared with healthy donors, patients with SLE had higher numbers of T-bethiCXCR3lo effector cells and T-bet+Foxp3lo non-suppressive cells, which excessively produce IFN-γ, and lower number of non-IFN-γ-producing T-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…IFN-ɣ might also be implicated in central nervous system alterations observed in SLE [ 49 ]. Recently, it has been demonstrated that IFN-ɣ production by T-bet + CD4 + cells is regulated by metabolic regulators, such as fatty acid synthesis inhibitors [ 50 ]. In keeping with our data, Kaplan and colleagues showed that, in splenocytes derived from CB 1 −/− /CB 2 −/− mice, treated in vitro with 2-AG, the IFN-ɣ secretion was reduced [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-ɣ might also be implicated in central nervous system alterations observed in SLE [ 49 ]. Recently, it has been demonstrated that IFN-ɣ production by T-bet + CD4 + cells is regulated by metabolic regulators, such as fatty acid synthesis inhibitors [ 50 ]. In keeping with our data, Kaplan and colleagues showed that, in splenocytes derived from CB 1 −/− /CB 2 −/− mice, treated in vitro with 2-AG, the IFN-ɣ secretion was reduced [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, mitochondria in SLE produce less ATP compared to healthy controls (HC) even though they are hyperpolarized ( 26 ). Additionally, evidence suggests that there are significant differences in glutamine ( 27 ) and lipid metabolism ( 28 ) in SLE T cells. A subset of CD4 + T cells producing IL-17 (Th17 cells) is expanded in SLE patients.…”
Section: Pathogenic Rewiring Of T Cells In Slementioning
confidence: 99%
“…Through cytokine and regulatory T cell (T-reg) mediated pathways, 2-DG exhibits anti-inflammatory properties. By increasing the production of cytokine production (IL-2) and preventing CTLA-4, a T-reg suppressor, 2DG therapy enhanced T-reg function [ 124 , 125 ]. According to a study, 2-DG inhibited the PI3K/Akt pathway to reduce TNF production during the early stages of inflammation [ 126 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%